Bread Production and Bakery Products in Russia: Current State and Prospects - Kiryuhina A.; Grigor'eva R.; Kozhevnikova A. (Техника и технология пищевых производств)
The transformation of the Russian economy has led to a significant reduction in the production of bread and bakery products. The recent years have seen a groing competition between retail chains, mini-bakeries, and bakeries. The present research features the problems of the production of bread and bakery products by large industrial enterprises and offers a number of possible solutions. The authors used statistical methods of data analysis. The study employed statistical data on the production volumes of bakery and flour confectionery products according to the Russian National Classifier of Types of Economic Activity as obtained from the Federal State Statistics Service. The study revealed the relationship between the deterioration of the economic situation in the country and the increase in the production of bread and bakery products, which confirms the social importance of bread. The reduction in the volume of bread and bakery products is connected with the annual decrease in the production of non-durable storage products by 1.3–2%. In 1990–2017, the volume of production decreased from 18.2 to 6.5 million tons. Low economic indicators remain a major problem of the baking industry. In 2017, the baking industry of the Kemerovo region showed the following levels: the use of average annual capacity – 35%, profitability – 2.5%, equipment wear – 50–80%. The production of long-term storage and low humidity products increases annually. In 2010-2017, the volume of production increased by 28.78%, and in 2017 it amounted to 552,000 tons. In 2010–2017, there was an increase in the production of flour confectionery products of long-term storage by 45%; the annual increase was 4–6%. In 2010–2017, production of flour confectionery products increased from 1.43 to 1.92 million tons. The research proved that it is advisable to divide the production of bakery and flour confectionery products into socially significant and commercial products. The authors believe that socially important products should include bakery products of short-term storage, as well as healthy foods with vegetable additives. As for commercial products, bakery products of long-term storage and low humidity should include products with a complex unique recipe, e.g. gluten-free bakery and confectionery products. To solve this problem, Kemerovo State University is currently developing scientifically based recipes and technologies for bakery products fortified with iodine, selenium, and various natural additives, e.g. sea buckthorn, cranberry, viburnum, etc.